A Study of Electrocyclic Reactions in a Molecular Junction: Mechanistic and Energetic Requirements for Switching in the Coulomb Blockade Regime. Issue 12 (5th May 2017) - Olsen, Stine T.; Brøndsted Nielsen, Mogens; Hansen, Thorsten; Ratner, Mark A.; Mikkelsen, Kurt V.
Abstract: Molecular photoswitches incorporated in molecular junctions yield the possibility of light‐controlled switching of conductance due to the electronic difference of the photoisomers. Another isomerization mechanism, dark photoswitching, promoted by a voltage stimulus rather than by light, can be operative in the Coulomb blockade regime for a specific charge state of the molecule. Here we elucidate theoretically the mechanistic and thermodynamic restrictions for this dark photoswitching for donor–acceptor substituted 4 n and 4 n +2 π‐electron open‐chain oligoenes (1, 3‐butadiene and 1, 3, 5‐hexatriene) by considering the molecular energies and orbitals of the molecules placed in a junction. For an electrocyclic ring closure reaction to occur for these compounds, we put forward two requirements: a) the closed stereoisomer ( cis or trans form) must be of lower energy than the open form, and b) the reaction pathway must be in accordance to the orbital symmetry rules expressed by the Woodward–Hoffmann rules (when the electrodes do not significantly alter the molecular orbital appearances). We find these two requirements to be valid for the dianion of (1 E, 3 Z, 5 E )‐hexa‐1, 3, 5‐triene‐1, 6‐diamine, and the Coulomb blockade diamonds were therefore modeled for this compound to elucidate how a dark photoswitching event would manifest itself in the stability plot. From this modeling of conductance as a function of gate and bias potentials, we predict a collapse in Coulomb diamond size, that is, a decrease in the height of the island of zero conductance. Abstract : Photoswitches in a molecular junction : The mechanistic and thermodynamic restrictions for dark photoswitching are theoretically elucidated for substituted oligoenes.